2022
DOI: 10.1073/pnas.2024357119
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sources and pathways for citrate secreted by human prostate cancer cells determined by NMR tracing and metabolic modeling

Abstract: Significance The human prostate accumulates high luminal citrate levels to serve sperm viability. There is only indirect qualitative evidence about metabolic pathways and carbon sources maintaining these levels. Human citrate-secreting prostate cancer cells were supplied with 13 C-labeled substrates, and NMR spectra of extracellular fluid were recorded. We report absolute citrate production rates of prostate cells and direct evidence that glucose is the main carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 81 publications
5
26
0
Order By: Relevance
“…1a). Similar studies using 13 Cglucose and -glutamine in cultured cells have shown that 3 to 6 hours of label exposure is sufficient for isotopic steady state 25,26 . We separately noted that doubling of media volume to 2 mL was necessary for a 12 to 24 hour experiment, in order to maintain media substrates above 50% (Extended Data Fig.…”
Section: Glucose and Glutamine Are The Major Tca Cycle Carbon Sources...mentioning
confidence: 60%
See 3 more Smart Citations
“…1a). Similar studies using 13 Cglucose and -glutamine in cultured cells have shown that 3 to 6 hours of label exposure is sufficient for isotopic steady state 25,26 . We separately noted that doubling of media volume to 2 mL was necessary for a 12 to 24 hour experiment, in order to maintain media substrates above 50% (Extended Data Fig.…”
Section: Glucose and Glutamine Are The Major Tca Cycle Carbon Sources...mentioning
confidence: 60%
“…In contrast, extracellular [U- 13 C]-palmitate contributed less than 15% of carbons to TCA cycle metabolites (Fig, 1f and Extended Data Fig. 1c-d).…”
Section: Glucose and Glutamine Are The Major Tca Cycle Carbon Sources...mentioning
confidence: 96%
See 2 more Smart Citations
“…Magnetic resonance spectroscopy and mass spectrometry are currently popular techniques for metabolic phenotyping in biological and medical settings. Despite their advantages, these techniques are not suitable for sensing metabolites at the point of care due to heavy reliance on high-cost advanced equipment and professional technicians. In this regard, surface-enhanced Raman spectroscopy (SERS) has emerged as a promising optical technique that allows for sensitive detection of metabolites by enhancing the Raman signals of molecules, mainly via excitation of the localized surface plasmon resonance (LSPR) of metal nanostructures. Especially, over 100 medically relevant metabolites can be catalyzed by specific enzymes to generate stoichiometric H 2 O 2 , a reactive compound that can be quantified by optical probes operating through activity-based sensing, such as through H 2 O 2 -mediated boronate oxidation. For example, we and other groups have developed boronate-based SERS nanoprobes enabling detection of H 2 O 2 and many different metabolites in body fluids, living cells, and tissues. Nevertheless, these SERS assays are not compatible with practical large-scale metabolic assays because synthesis of nanoprobes is labor-intensive, and more importantly, can suffer from batch-to-batch variability.…”
Section: Introductionmentioning
confidence: 99%